2020
DOI: 10.1161/jaha.119.015616
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of PAR‐1 Signaling Attenuates Cardiac Hypertrophy and Fibrosis in Renin‐Overexpressing Hypertensive Mice

Abstract: Background Although PAR‐1 (protease‐activated receptor‐1) exerts important functions in the pathophysiology of the cardiovascular system, the role of PAR ‐1 signaling in heart failure development remains largely unknown. We tested the hypothesis that PAR ‐1 signaling inhibition has protective effects on the progression of cardiac remodeling induced by chronic renin–angiotensin system activation using renin‐overexpressing hypertensive (Ren‐Tg) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…It has been previously reported that activators or blockers of thrombin-activated PAR-1 evoke a decrease and increase in blood pressure in healthy animals, respectively [28], whereas the blockade of PAR-1 in renin-overexpressing mice reduces hypertension [29]. Moreover, PAR-1 receptors in the vasculature are known to contribute to endotheliummediated vasodilatation and smooth muscle cell (SMC)-mediated vasoconstriction [30].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that activators or blockers of thrombin-activated PAR-1 evoke a decrease and increase in blood pressure in healthy animals, respectively [28], whereas the blockade of PAR-1 in renin-overexpressing mice reduces hypertension [29]. Moreover, PAR-1 receptors in the vasculature are known to contribute to endotheliummediated vasodilatation and smooth muscle cell (SMC)-mediated vasoconstriction [30].…”
Section: Discussionmentioning
confidence: 99%
“…PAR-1-knockout mice treated with a subpressor dose of Ang II for 4 weeks failed to cause vascular remodeling of the aorta but did induce cardiac hypertrophy, in contrast to the effect on wild-type mice, indicating that PAR-1 plays a significant role in "vascular" remodeling induced by Ang II without raising blood pressure. Narita et al also previously demonstrated cardioprotective effects of PAR-1 inhibition by SCH79797, a PAR-1 antagonist, on cardiac hypertrophy and fibrosis in Ren-2 mice [7]. They also showed that the FXa-induced enhancement of hypertrophic signaling in isolated cardiac fibroblasts was abolished by SCH79797, indicating that both PAR-1 and PAR-2 are activated in association with FXa in Ren-2 mice.…”
mentioning
confidence: 85%
“…Activation of protease-activated receptor-1 (PAR1), which couples to Gq/11, Gi/o, and G12/13, elevates the level of profibrotic gene expression in rat cardiac fibroblasts, leading to myofibroblast activation and increasing collagen synthesis by 60% ( 48 ). Conversely, inhibiting PAR1 with SCH79797 attenuates cardiac fibrosis and hypertrophy in the renin-overexpressing induced hypertensive mice model ( 16 ). However, PAR1 is highly expressed in platelets, and its antagonist is used for antiplatelet therapy ( 49 ).…”
Section: Gpcrs Expressed On Cardiac Fibroblastsmentioning
confidence: 99%